Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1111/j.1574-695x.2010.00725.x
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Candida albicans to photodynamic action of 5,10,15,20-tetra(4-N-methylpyridyl)porphyrin in different media

Abstract: The photodynamic activity of 5,10,15,20-tetra(4-N-methylpyridyl)porphyrin (TMPyP) was evaluated in vitro on Candida albicans cells under different experimental conditions. This tetracationic porphyrin binds rapidly to C. albicans cells, reaching a value of ∼1.7 nmol 10(-6) cells when the cellular suspensions (10(6) CFU mL(-1) ) were incubated with 5 μM sensitizer. The amount of cell-bound sensitizer is not appreciably changed when cultures are incubating for longer times (>15 min) but it diminishes with the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 31 publications
(43 reference statements)
2
32
0
Order By: Relevance
“…Yeast cultures treated without addition of the tested porphyrins, but illuminated with the same intensities of blue light (light control) showed no significant decrease in viability (about 0.2 orders of magnitude). Similar results of phototreatment of C. albicans with the cationic and anionic porphyrins were reported by other groups (13–15).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Yeast cultures treated without addition of the tested porphyrins, but illuminated with the same intensities of blue light (light control) showed no significant decrease in viability (about 0.2 orders of magnitude). Similar results of phototreatment of C. albicans with the cationic and anionic porphyrins were reported by other groups (13–15).…”
Section: Resultssupporting
confidence: 89%
“…It can be concluded that the penetration of the charged porphyrins into the yeast cells is dependent not only on the quantity of the proteins in the medium, but also on the quality. In another study, TMPyP was shown to efficiently photoinactivate C. albicans in liquid medium (Sabouraud broth) and on agar‐plate (Sabouraud agar) surface (15). As the Sabouraud medium is similar to NB, it is not surprising that the results are similar to those in the present study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently a new Pp, the tetracationic porphyrin 5,10,15,20‐tetra(4‐N‐methylpyridyl) porphyrin (TMPγP) demonstrated a high in vitro effectiveness for photodynamic inactivation of C. albicans colonies in both liquid suspensions and localized on a surface (52).…”
Section: Photosensitizersmentioning
confidence: 99%
“…Porphyrins and metalloporphyrins are of great importance due to their role in numerous chemical, biological, and medical processes . For example, porphyrins represent medically active compounds in the photodynamic therapy of cancer and human immunodeficiency virus (HIV) .…”
Section: Introductionmentioning
confidence: 99%